2021
DOI: 10.1051/jnwpu/20213961296
|View full text |Cite
|
Sign up to set email alerts
|

Research on Taylor impact fracture behavior of ZrCuAlNiNb amorphous alloy

Abstract: Under argon conditions, the Taylor impact test for ZrCuAlNiNb amorphous alloy with impact velocity range of 78.9-155 m/s was carried out, the failure fracture process of the material was recorded by high-resolution high-speed photography, and the fractured samples after fracture were recovered. The microscopic morphology of the section was observed by scanning electroscope, and the fracture behavior of the material at different impact speeds was analyzed. ZrCuAlNiNb amorphous alloy breaks from a single main sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…According to the recovered fracture samples, it is found that the fracture surface is not a relatively smooth surface in the height direction, and its fracture surface is uneven. This is because the fracture of the material is a process of damage accumulation, which can be expressed by the combination of macro-micro simulation [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…According to the recovered fracture samples, it is found that the fracture surface is not a relatively smooth surface in the height direction, and its fracture surface is uneven. This is because the fracture of the material is a process of damage accumulation, which can be expressed by the combination of macro-micro simulation [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…15(d). This indicates that the brittle-tough transition phenomenon [36,37] occurs at the edge locations of the fragments due to the axial stretching of the shock wave and the radial stress of the surrounding fragments [16] at high strain rates, which is the first to produce fracture. But the phenomenon in the intermediate position is due to the micro-damage aggregation reaching a certain proportion at this time, and the micro-damage aggregation reaching a certain proportion, resulting in the direct fracture of the fragments [13,14].…”
mentioning
confidence: 99%